Cabinet of ludicrosity - Sng, Issa Yi Xian (2018)
Cabinet of Ludicrosity is an interactive installation comprising various ludicrous contraptions and curiosities. Based on the Kunstkammer (German term for ‘art chamber’ or cabinet of curiosities) which flourished in 16th century Europe, the installation is simultaneously a workshop, a collection and a playroom. The seemingly diverse objects and devices are united by an underlying spirit of play and ludicrousness. Innocently irreverent, the Cabinet of Ludicrosity celebrates the impractical, trivial and absurd amidst our preoccupation with utility and significance.